Linking software engineering paradigms to Islamic values - Khan, Burhan Ul Islam; Pampori, Bisma Rasol; Mattoo, M. Mueen Ul Islam; Hurrah, Ajaz Ahmad; Ajayi, Binyamin Adeniyi; Olanrewaju, Rashidah Funke (Journal of Theoretical and Applied Information Technology, 2017)
In general, Muslims all over the world have an innate tendency to hold fast to Islam’s teachings as narrated